Super twisting sliding mode control algorithm for developing artificial pancreas in type 1 diabetes patients. (September 2017) - Ahmad, Sayyar; NasimUllah,; Ahmed, Nisar; Ilyas, Muhammad; Khan, Waqas
Highlights: Super twisting sliding mode control algorithm for developing artificial pancreas in type 1 diabetes patients. Detailed global stability proof is presented. Comparative study and analysis of the proposed super twisting algorithm with classical sliding mode control. Abstract: Diabetes mellitus is one of the most common disease in the world. Specifically, juvenile diabetes in which pancreas of patient does not produce insulin that results in high concentration of glucose in the blood plasma for longer periods of time. High concentration of the glucose can cause many complications and may lead to the death. For this purpose optimal control of the blood glucose concentration is required in type 1 diabetes patients. In this research work closed loop control algorithm is proposed based on the sliding mode control (SMC) for type 1 diabetes patient. Bergmans minimal model is presented for studying dynamical behaviour of the glucose and insulin inside human body. Control mechanism based on classical SMC is designed and compared with the super twisting control algorithm which is based on the higher order SMC. A common drawback of classical SMC is the high frequency chattering in control signal which is minimized by using super twisting SMC approach. Super twisting SMC controller is designed and subjected to external disturbances for verifying the required robustness of the closed loop. A comparative analysis of the classical SMC and super twisting SMC is given in results section. Meal disturbance to diabetes patient is also explicitly explained and is given in simulation results. Numerical simulation results are provided to show the superiority and the advantages of the proposed controller such as robustness to external disturbances, no chattering, less control effort and accurate output tracking, thus proposed controller can be considered as a suitable choice for designing automatic insulin pumps for diabetes patients.